Fenomena Kenakalan Remaja dan Kriminalitas Kasus Tawuran di Bekasi (Studi Literature Review) - Aldi Riyanto; Andriyani Andriyani; Leo Permana; Mahdav Viqiyan Sirlani; Lika Rahmaningrum; Mic Finanto Ario Bangun (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This study reviews the phenomenon of juvenile delinquency and crime in the context of brawl cases in Bekasi. Through a literature review, various factors are examined which are the causes and impacts of teenage brawls in the city. First, social factors such as economic instability, lack of education, and a family environment that is not conducive can trigger juvenile delinquency. Second, environmental factors, including peers and the influence of mass media, also contribute to aggressive adolescent behavior. In addition, psychological factors such as lack of self-control and the need for affiliation also play a role in the formation of criminal behavior. The impact of teenage brawls includes social, economic and psychological losses for individuals and the surrounding community. This study highlights the important role of families, schools and social institutions in preventing and overcoming the phenomenon of juvenile delinquency and brawling crimes in Bekasi. With an in-depth understanding of the factors that influence adolescent behavior, it is hoped that effective intervention strategies can be formulated to reduce cases of brawls and improve the quality of life of adolescents in Bekasi.